2014
DOI: 10.1016/j.jdent.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The decision to repair or replace a defective restoration is affected by who placed the original restoration: Findings from the National Dental PBRN

Abstract: Objectives To evaluate how restoration characteristics are associated with the decision to repair or replace an existing restoration. The following hypotheses were studied: Dentists who placed the original restoration are more likely to repair instead of replace restorations (H1) that are in molar teeth; (H2) that are in the upper arch; (H3) that have amalgam restorative material; (H4) if a fracture is not the primary reason for the defect; and (H5) when the restoration comprises more than one surface. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 42 publications
0
17
0
3
Order By: Relevance
“…Previous studies showed that restorations that were repaired due to fracture had a lower survival rate than restorations that were repaired due to other reasons 7, 2930 . Fracture as a reason for failure and amalgam as a restorative material may jointly exert negative influences on the survival of restorations 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that restorations that were repaired due to fracture had a lower survival rate than restorations that were repaired due to other reasons 7, 2930 . Fracture as a reason for failure and amalgam as a restorative material may jointly exert negative influences on the survival of restorations 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The probable cause of this difference is that amalgam restorations cannot retain a dental material and tooth surface chemically, but RBCs can be bond each other [22]. In addition, the reason which increased the decision may be that amalgam has not sufficient aesthetic quality compatible with tooth colour [23].…”
Section: Resultsmentioning
confidence: 99%
“…Deciding when and in which way to intervene appears to be inconsistent among dentists as they do not always use objective criteria (Bader and Shugars 1993 ;Gordan et al 2015 ). Deciding when and in which way to intervene appears to be inconsistent among dentists as they do not always use objective criteria (Bader and Shugars 1993 ;Gordan et al 2015 ).…”
Section: How To Manage a Defective Restorationmentioning
confidence: 99%